2021
DOI: 10.3991/ijim.v15i10.21137
|View full text |Cite
|
Sign up to set email alerts
|

Gamification Design Elements to Enhance Adolescent Motivation in Diagnosing Depression

Abstract: Depression is a critical public health problem, mainly when it affects young people (adolescents). This condition is most challenging to detect in this group because they tend to think about other people's negative assumptions. Adolescents with depressive symptoms refuse to seek professional help due to their stigma and their future if they were labeled as depressed teenagers. Depression is a severe mental issue that should be detected from an early stage so that the problem can be curbed and resolved immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The synthesis of the gamification elements with content analysis techniques from articles and research papers (Al-Smadi, 2015;Boyinbode, 2018;Daungtod et al, 2020;Jamaludin et al, 2021;Poondej et al, 2016;Yamani, 2021). This consists of two main elements and eleven sub-elements as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the gamification elements with content analysis techniques from articles and research papers (Al-Smadi, 2015;Boyinbode, 2018;Daungtod et al, 2020;Jamaludin et al, 2021;Poondej et al, 2016;Yamani, 2021). This consists of two main elements and eleven sub-elements as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, because gamification is still in its infancy, there is often a lack of a theoretical underpinning for some of the gamification proposals [44]. Consequently, recent studies have shown an interest in the use of theory in the gamification of various domains [45]. Likewise, several studies have used design models when gamifying systems.…”
Section: Theories and Models Used In Gamificationmentioning
confidence: 99%
“…The majority of research endeavors have focused on enhancing cognitive behavioral therapy (CBT) techniques across skills by incorporating a variety of gamification elements. 15 , 16 , 19 22 Only one study 26 has utilized the Hexad theory with gamification components but for diagnosis rather than treatment. Although the hexad theory idea is well-known in the field of user experience design, its application in treatment—specifically, in games that are based on CBT—is still relatively new.…”
Section: Introductionmentioning
confidence: 99%